Comparing Employability Skills of Technical and Vocational Education Students of Thailand and Malaysia: A Case Study of International Industrial Work-Integrated Learning - Sa-Nguanmanasak, Theerasak; Khampirat, Buratin (Journal of Technical Education and Training, 2019)
This study focused on a comparison of technical and vocational education (TVE) students' employability skills in Thailand, a newly industrialized country and ranked 61st out of 148 countries worldwide on the quality of graduatesâ€™ skillsets, and Malaysia, a top-ranked country in the group of upper-middle income countries in terms of graduatesâ€™ skillsets (6th). Thirty mentors were asked to assess 90 Thai and 83 Malaysian students who completed international work-integrated learning (WIL) programs in 2015, 2016, 2017 and 2018, using a questionnaire that addressed 16 main aspects of measuring employability skills. The findings indicated that most of the Malaysian students had better employability skills than Thai students and there were no significant differences in employability skills between male and female students in both countries.  The regression model of quality of work indicated that â€˜ability to learn and apply knowledgeâ€™, â€˜judgment and decision makingâ€™, â€˜discipline and adaptability to a formal organizationâ€™, â€˜ethics and moralityâ€™ and â€˜quantity of workâ€™ had a positive effect on â€˜quality of workâ€™. This study suggested that, in order to effectively prepare students for professional work and careers in ever-changing workplaces, TVE institutions should carefully assess the quality of the WIL environment, especially international WIL. The reflection of mentors in the workplace provided useful information for TVE institutions to develop effective WIL program to boost studentsâ€™ qualities and may give insight into how students are likely to receive sustainable employment development to building a more sustainable society through the skills and knowledge of their students.